Challenges of Physiotherapist During Prosthesis Rehabilitation in Malaysia - Chong, Li Chi; Vinodhkumar, Ramalingam (Horizon Publisher India, 2021)
The present study reported the challenges faced by the physiotherapist during prosthesis rehabilitation in Malaysia. Mortality due to lower limb amputation is a concern in recent days that can be improved by providing proper rehabilitation. However, challenges faced by the physiotherapist during rehabilitation are expected to affect the effectiveness of the rehabilitation. Hence, it is important to identify the possible challenges faced by the physiotherapist during prosthesis rehabilitation to take the necessary precautions for better outcomes. A total of 200 Malaysian physiotherapists who have experience in rehabilitating amputees were selected to participate in this online survey. The participants were requested to complete a self-administered electronic questionnaire containing 20 questions. The present study reported a few challenges faced by the physiotherapists in Malaysia during prosthesis rehabilitation such as “encountering patient that refuse to perform exercises is common” (77%), encountered high physical demand (81.5%), encountering language barriers (48.5%), patients often encounter difficulty in assessing health service (63.5%) and encountering prosthesis problems (67%). The barriers were inconsistent and complex, including patient factors, healthcare provider’s factors, environmental factors, other factors. The study has highlighted challenges faced by the physiotherapists during prosthesis rehabilitation to raise awareness among physiotherapists and at the same time create ideas for specific health care practitioners to overcome the barriers, therefore shortening the length of rehabilitation and enhancing the effectiveness of the rehabilitation to lower the mortality.